2021
DOI: 10.5944/rppc.28090
|View full text |Cite
|
Sign up to set email alerts
|

Predictores de síntomas de ansiedad, depresión y estrés a partir del brote epidémico de COVID-19

Abstract: Predictors of anxiety, depression, and stress symptoms from the COVID-19 outbreakAbstract: The COVID-19 pandemic has caused an unprecedented global crisis, with dramatic changes in people’s living conditions and mental health. The aim of this study is to establish predictors of depression, anxiety and stress in people affected by the epidemiological outbreak of COVID-19. Participants comprised 2,376 individuals over 18 years old, 79.6% women, who answered the Scale of Depression, Anxiety and Stress (DASS-21), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
13
0
6
Order By: Relevance
“…A recent meta-analysis reported by Salari et al (2020) based on 17 studies of the general population found that the prevalence of anxiety and depression, as a result of the COVID-19 pandemic, was 31.9 and 33.7%, respectively. Similar results have been found in studies of the general population conducted in Spain (Hidalgo et al, 2020;Sandín et al, 2020cSandín et al, , 2021Gutiérrez-Hernández et al, 2021) and Hispanic American countries (Andrades-Tobar et al, 2021;Mestas et al, 2021) since the COVID-19 pandemic, as well as in children and adolescents (Gómez-Becerra et al, 2020;Orgilés et al, 2020bOrgilés et al, , 2021Pedreira, 2020). The existing literature on the impact of COVID-19 in adolescents is generally limited, and evidences the relevance of researching this issue (e.g., Muzi et al, 2021), including the role of emotion regulation strategies (Velotti et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…A recent meta-analysis reported by Salari et al (2020) based on 17 studies of the general population found that the prevalence of anxiety and depression, as a result of the COVID-19 pandemic, was 31.9 and 33.7%, respectively. Similar results have been found in studies of the general population conducted in Spain (Hidalgo et al, 2020;Sandín et al, 2020cSandín et al, , 2021Gutiérrez-Hernández et al, 2021) and Hispanic American countries (Andrades-Tobar et al, 2021;Mestas et al, 2021) since the COVID-19 pandemic, as well as in children and adolescents (Gómez-Becerra et al, 2020;Orgilés et al, 2020bOrgilés et al, , 2021Pedreira, 2020). The existing literature on the impact of COVID-19 in adolescents is generally limited, and evidences the relevance of researching this issue (e.g., Muzi et al, 2021), including the role of emotion regulation strategies (Velotti et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…Women, on the other hand, have shown higher levels of anxiety than men [ 49 ]; however, men have stood out as suffering more depression than women [ 50 ]. In terms of age, higher measures of stress, anxiety and depression are found in younger students than in older ones [ 51 ].…”
Section: Impact Of Covid-19 On the Educational Scenariomentioning
confidence: 99%
“…Physical distancing, prevention measures, the vaccination process, and quarantine confinement have had a significant impact on the social, economic, physical, and mental aspects of people (Organización Mundial de la Salud, 2020; CEPAL, 2021). In the latter, increases in depressive, anxious, and academic stress symptoms have been identified, as well as alterations in sleep and eating routines, all of which affect the wellbeing of university students (Bao et al, 2020;Andrades-Tobar et al, 2021;Sekban and İmamoğlu, 2021).…”
Section: Introductionmentioning
confidence: 99%